Work-life Balance Initiatives of Employees’ Women in Development Banks of Nepal: Employees’ Perspective - Parajuli, Pradip (Journal of Population and Development, 2021)
Work-life balance (WLB) is almost helping employees in maintaining healthy, rewarding lifestyles that will, in turn, lead to improvements in efficiency or prosperity. The study intended to explore the level of satisfaction of the working women on their personal commitments, to evaluate the workingwomen perception on support of senior officials and to identify employee’s women perspective on balance work load. This study has been based on descriptive as well as exploratory research designs were used with sample size of 40. Data was collected from four development sector banks in Nepal through structured schedules, using convenience sampling. The study provides an insight to academicians and policy makers in bank and other organizations into the needs of today’s employees and initiatives taken in public sector banks for work-life balance. Other organizations might adopt these practices for helping employees attain work-life balance and hence increase their job satisfaction and organizational productivity.